Research Trends in High School Students' Self-Confidence in Indonesia - Dea Ananda Ratu Mughni; Ayu Wandira Ningsih; Andini Kesuma Destiana; Arma Nurhidayanto; Alrefi Alrefi; Akbari Akbari (Journal of Education and Counseling (JECO), 2023)
Self-confidence is important in the process of life to enable individuals to socialize with their living environment when facing life's challenges. Recognizing the importance of self-confidence, it is necessary to have new research and innovation in the field of research and knowledge development. The purpose of this study was to analyze the direction of self-confidence research in the last ten years in Indonesia to identify any new insights. The method used was content analysis. The sample consisted of articles published on Google Scholar and ResearchGate. The data analysis technique involved examining the titles, methods, and research findings. The findings of this study indicated that self-confidence had an impact on personal, academic, and career domains. Research on self-confidence was expected to contribute to future researchers in exploring self-confidence with other psychological aspects using different research methods.